2012
DOI: 10.1038/nature11554
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic amplification by dendritic spines enhances input cooperativity

Abstract: Dendritic spines are the nearly ubiquitous site of excitatory synaptic input onto neurons1–2 and as such are critically positioned to influence diverse aspects of neuronal signaling. Decades of theoretical studies have proposed that spines may function as highly effective and modifiable chemical and electrical compartments that regulate synaptic efficacy, integration, and plasticity3–8. Experimental studies have confirmed activity-dependent structural dynamics and biochemical compartmentalization by spines9–12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
311
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(342 citation statements)
references
References 36 publications
20
311
6
Order By: Relevance
“…However, besides this biochemical role, spines have also been hypothesized to play an electrical role, altering excitatory postsynaptic potentials (EPSPs) (22)(23)(24)(25)(26)(27)(28)(29)(30). Consistent with this idea, activating spines with two-photon uncaging of glutamate generates potentials whose amplitudes are inversely proportional to the length of the spine neck (31), and these responses are much larger in spines than in adjacent dendritic shafts (32). Also, spine conductances can be activated independently of dendritic ones (33)(34)(35)(36).…”
mentioning
confidence: 48%
“…However, besides this biochemical role, spines have also been hypothesized to play an electrical role, altering excitatory postsynaptic potentials (EPSPs) (22)(23)(24)(25)(26)(27)(28)(29)(30). Consistent with this idea, activating spines with two-photon uncaging of glutamate generates potentials whose amplitudes are inversely proportional to the length of the spine neck (31), and these responses are much larger in spines than in adjacent dendritic shafts (32). Also, spine conductances can be activated independently of dendritic ones (33)(34)(35)(36).…”
mentioning
confidence: 48%
“…Previous studies based on EM 25 or diffusion measurements 9 reported a range of 1 to 400 MΩ for R neck , whereas a recent study based on Ca 2+ imaging estimated R neck to be relatively large (500 MΩ) and to very little across spines, which suggests that morphology does not a play a major 16 role 44 . Encompassing these values, our measurements revealed a broad distribution, indicating that, at any given time, half of all spines have R neck values larger than 56 MΩ, with 5% having resistances larger than 500 MΩ.…”
Section: Reliable Estimates Of Spine Neck Resistancementioning
confidence: 86%
“…Spines with shorter and wider necks will 18 be able to sustain stronger synaptic currents, because the driving force will be effectively maintained even during large or repeated synaptic conductance changes. In this way, the observed neck changes may functionally disinhibit the synapse, which could contribute to synaptic weight changes during LTP 44,49 . Taken together, our findings challenge the widespread notion that spines primarily shape biochemical rather than electrical signaling at synapses.…”
mentioning
confidence: 99%
“…A major finding is that spine heads are not isopotential with the parent dendrite, implying that spine heads are quasiindependent electrical compartments [18]. Importantly, however, the NMDA spike that occurs in the spine head requires both synaptic input to that spine and depolarization from other spines, thus implementing the Hebbian association.…”
Section: (A) Short-term Potentiationmentioning
confidence: 99%